THE VOICE OF AN EDUCATOR FROM AN EARLY CHILDHOOD EDUCATION SCHOOL IN LATIN AMERICA, INSPIRED BY THE PHILOSOPHY OF LORIS MALAGUZZI - Gabriel, Aparecida Garcia Pacheco; da Silva, Jacqueline Silva; Martins, Silvana Neumann (Seven Editora, 2025)
This work presents an analysis of educational practices inspired by the philosophy of Loris Malaguzzi, developed by a pedagogist and atelierist who works at the Casa da Infância School in the city of Salvador, Bahia in Latin America The results of the educator's educational practice show how the approximation with the educational principles of Loris Malaguzzi's philosophy are translated into learning strategies,  Through the hundred languages of the child, listening, investigation, documentation and participation, they made an approximation with the approach used in early childhood education schools in Reggio Emilia/Italy, demonstrating how this educational practice enhances and favors the learning of children in Latin America, developing creativity, autonomy, entrepreneurial behavior and child protagonism.DOI: https://doi.org/10.56238/sevened2024.037-136